Hubungan Pemahaman Konsep Pecahan dan Aturan Radd Dalam Ilmu Fara’idh terhadap Kemampuan Siswa dalam Menyelesaikan Masalah Pembagian Harta Warisan - Khaerul Iqbal Juhdi; Indah Nursuprianah; Muhamad Ali Misri (LP2M IAIN Syekh Nurjati Cirebon, 2017)
This study starts from the number of people around us who are still goingscience, fara'idh but the science is very important to be studied, understood and practiced especially among the Muslim community, but in reality both in our own neighborhood much practice division of inheritance is not based applicable law.Elderly ancient proverb says